2006
DOI: 10.1002/jnr.21135
|View full text |Cite
|
Sign up to set email alerts
|

Aβ(25–35) and its C‐ and/or N‐blocked derivatives: Copper driven structural features and neurotoxicity

Abstract: The toxic properties of beta-amyloid protein, Abeta(1-42), the major component of senile plaques in Alzheimer's disease, depend on nucleation-dependent oligomerization and aggregation. In addition, Abeta(1-42) toxicity is favored by the presence of trace metals, which affect the secondary structure of the peptide. A peptide comprising 11 residues within Abeta(1-42) [Abeta(25-35)] aggregates and retains the neurotoxic activity of Abeta(1-42). We have used both Abeta(25-35) and its C-amidated or N-acetylated/C-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Rat cortical cultures, both pure neuronal and mixed neuron-glial types, were challenged either with soluble aggregates of the active A␤ fragment, A␤(25-35), (Giuffrida et al, 2007) or oligomers of the full-length A␤(1-42) . A␤(25-35) and A␤(1-42) were used at concentrations of 25 M and 100 nM, respectively, which induced a similar extent of neuronal death (35-45%) over a 24-h period.…”
Section: Resultsmentioning
confidence: 99%
“…Rat cortical cultures, both pure neuronal and mixed neuron-glial types, were challenged either with soluble aggregates of the active A␤ fragment, A␤(25-35), (Giuffrida et al, 2007) or oligomers of the full-length A␤(1-42) . A␤(25-35) and A␤(1-42) were used at concentrations of 25 M and 100 nM, respectively, which induced a similar extent of neuronal death (35-45%) over a 24-h period.…”
Section: Resultsmentioning
confidence: 99%
“…5) (Giuffrida et al, 2007;Damante et al, 2008), Zn (Zirah et al, 2003;Damante et al, 2009;Drochioiu et al, 2009), Fe(II) and Fe(III) (Drochioiu, 2009). The latter complexes are so strong that it has been suggested that Ab could compete for iron against other iron-containing proteins such as transferrin to greatly interfere with this metal homeostasis (Jiang et al, 2009).…”
Section: Ab Interaction With Metalsmentioning
confidence: 94%
“…Before Aβ 1–42 (Sigma-Aldrich, USA) was used, it was firstly incubated in sterile saline at 37°C for 7 days to allow the change in an assembly state of the peptide with ensuing toxicity [18]. The incubated Aβ 1–42 solutions generally contain both fibril-like structures and different-sized oligomers [19]. Rats, which had been deeply anesthetized with pentobarbital (55 mg/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%